Is compliance with lifestyle modifications dependent on sociodemographic factors and awareness of HF symptoms? Impact of lifestyle changes on HF patients’ wellbeing. - Krzyżanowska, Marta Olga; Moryson, Wacław Bernard; Prokop, Edyta; Migaj, Jacek; Grajek, Stefan (Journal of Medical Science, 2017)
Aim. The aim of this study was to obtain information, whether patients with heart failure (HF) follow medical indications and if there are any sociodemographic differences between compliant and noncompliant patients and how lifestyle changes contribute to the patients’ wellbeing.Material and Methods. A survey was carried out in 198 patients hospitalized in I Clinic of Cardiology in Poznan. Patients were divided into groups: P1- no lifestyle changes, P2- 1 of 4 verified lifestyle modifications, P3- 2 or 3 verified lifestyle modifications, P4- all 4 verified lifestyle modifications.Results. People over the age of 65 mostly constitute groups of low compliance (p = 0,055). Men are more eager to change their lifestyle (91,4% in P3 and 85,7% in P4). Women belong mainly to groups with low compliance (p = 0,0001). Respondents who reported condition improvement were less likely to describe decreased sexual activity (59,6% vs 38,2%, p = 0,078), which acted as an important determinant of family relations. However, our analysis demonstrated a non-significant impact of adherence to indicated lifestyle modifications on patients’ wellbeingConclusions. Compliant patients are statistically younger and more often male. Level of education is the least important determinant of compliance. There is no significant impact of adherence to indicated lifestyle modifications on patient’s wellbeing. Compliant patients are less likely to reduce their sexual activity, which showed to be an important family relationship factor.